An experimental study of sex segregation in the Swedish labour market: is discrimination the explanation? - Magnus Carlsson; Dan-Olof Rooth (Institute for the Study of Labor (IZA), 2008)
This paper studies whether sex discrimination is the cause of sex segregation in the Swedish labour market. The correspondence testing (CT) method was used, which entails two qualitatively identical applications, one with a female name and one with a male name, being sent to employers advertising for labour. The results show that females have a somewhat higher callback rate to interview in female-dominated occupations, while in male-dominated occupations there is no evidence of any difference. The conclusion is that the sex segregation prevailing in the Swedish labour market cannot be explained by discrimination in hiring. Instead, the explanation must be found on the supply side.
urn:nbn:de:101:1-20081126861
Keywords: J64; 330; Sex discrimination; segregation; exit from unemployment; Personalbeschaffung; Arbeitsmarktdiskriminierung; Geschlechterdiskriminierung; Berufliche Integration; Test; Schweden